APPLICATION OF STORYTELLING TECHNIQUES IN ISLAMIC RELIGIOUS EDUCATION LEARNING - Santika, Santi; Syafaat, M Azis; Septiawan, Harzen (Amanah Publishing, 2024)
The implementation of story-based learning techniques also presents challenges, particularly related to teacher skills in conveying stories engagingly and effectively, as well as time management during the learning process. Teachers need to possess strong storytelling skills and master classroom management methods so that students can actively participate without losing focus on learning objectives. Therefore, teacher training and competency development are crucial for optimizing story-based learning techniques and maximizing their benefits in improving learning outcomes. Considering the various advantages and potential of story-based learning, this technique can be an effective solution to overcome student boredom with conventional learning methods that tend to be monotonous, such as lectures or memorization. This approach can create a dynamic and enjoyable classroom atmosphere, while also building students' character and communication skills holistically. Therefore, the development and implementation of story-based learning techniques need to be continuously encouraged at all levels of education as an effort to improve the overall quality of education.